Beneficial role of aminoguanidine on acute cardiomyopathy related to doxorubicin-treatment - Cigremis, Yilmaz; Parlakpinar, Hakan; Polat, Alaadin; Colak, Cemil; Ozturk, Feral; Sahna, Engin; Acet, Ahmet (Springer, 2006)
Doxorubicin (DOX) is a broad-spectrum anthracycline antibiotic that has cardiotoxicity as a major side effect. One mechanism of this toxicity is believed to involve the reactive oxygen radical species (ROS); these agents likely account for the pathophysiology of DOX-induced cardiomyopathy. Aminoguanidine (AG) is an effective antioxidant and free radical scavenger which has long been known to protect against ROS formation. We investigated the effects of AG on DOX-induced changes in thiobarbituric acid reactive substances (TBARS) and reduced glutathione (GSH) content. The rats were divided into four groups:1) Control; 2) DOX group; injected intraperitoneally (i.p.) with DOX 20 mg/kg in a single dose 3) AG-treated group; injected i.p. in single dose of 20 mg/kg DOX plus 100 mg/kg AG 1 h before the DOX for 3 days, 4) AG group; injected i.p. with AG 100 mg/kg for 3 days. DOX administration to control rats increased TBARS and decreased GSH levels. AG administration before DOX injection caused significant decrease in TBARS and increase in GSH levels in the heart tissue when compared with DOX only. Morphological changes, including severe myocardial fibrosis and inflammatory cell infiltration were clearly observed in the DOX-treated heart. AG reversed the DOX-induced heart damage. Therefore AG could protect the heart tissue against free radical injury. The application of AG during cancer chemotherapy may attenuate tissue damage and improve the therapeutic index of DOX.
Keywords: aminoguanidine; cardiomyopathy; doxorubicin; thiobarbituric acid reactive substances